REDEFINING OUR FORMAL EDUCATION - Tans, Feliks; Nalley, H. M.; Bhae, Yohanes (Academic Journal of Educational Sciences, 2020)
In this article we argue that our formal education has failed, to a certain extent, to create good quality graduates, namely, those whoare not only competent and independent, but also good in terms of such character traits as â€œgrit, self-control, zest, social intelligence, gratitude,optimism, and curiosityâ€ (Tough, 2012: 76). Such a failure has been caused by some educational practices which are not pedagogically soundlike: institutional manipulations leading to our studentsâ€™ highly consumeristic behaviours;nondialogical education; teacher-centered approach;misunderstanding of teaching and learning; and, centralised education.To prevent such a failure, we suggest that our formal educational systembe redefined so that it will be capable of creating good quality education that, in turn, can help our students be more competent, independent, andexcellent in terms of the character traits mentioned. It can be done by applying such methods as Ivan Illichâ€™s learning webs, Paulo Freireâ€™sdialogical education, and student-centered education in which teaching is seen as a means of faciliating studentsâ€™ learning based on theirpotentials, interests, and learning needs. In this sense, it is important that school curricula be also designed by each educational institution andthat each individual instituion has its own independent management system and networking system to make it more successful in achieving itseducational goals.